Toward Improved Understanding of Changes in Greenland Outlet Glacier Shear Margin Dynamics in a Warming Climate - Lampkin, Derrick J.; Parizek, Byron; Larour, Eric Y.; Seroussi, Hélène; Joseph, Casey; Cavanagh, John P. (Frontiers in Earth Science, 2018)
The Greenland Ice Sheet has experienced accelerated mass loss over the last couple decades, in part due to destabilization of marine-terminating outlet glaciers. Retreat and acceleration of outlet glaciers coincides with atmospheric and oceanic warming resulting in a significant contribution to sea-level rise. The relative role of surface meltwater production, runoff and infiltration on the dynamics of these systems is not well understood. To assess how surface meltwater impacts shear margin dynamics and regional ice flow of outlet glaciers, we investigate the impact of basal lubrication of Jakobshavn Isbræ shear margins due to drainage from water-filled crevasses. We map the areal extent of inundated crevasses during summer (May-August) from 2000 to 2012 using satellite imagery and determined an increasing trend in the total areal extent over this time interval. We use a numerical ice flow model to quantify the potential impact of weakened shear margins due to surface melt derived basal lubrication on regional flow velocities. Ice flow velocities 10 km from the lateral margins of Jakobshavn were amplified by as much as 20%, resulting in an increase of ~0.6 Gt yr-1 in ice-mass discharge through the shear margins into the ice stream. Under future warming scenarios with increased surface melt ponding, simulations indicate up to a 30% increase in extra-marginal ice flow. We conclude that surface meltwater will likely play an important role in the evolving dynamics of glacier shear margins and the future mass flux through Greenland’s major marine-terminating outlet glaciers.